COMPOSIÇÃO DA MEIOFAUNA NA ILHA DE ITAMARACÁ E SUA RELAÇÃO COM A DESCRIÇÃO MORFOSCÓPICA E MORFOMÉTRICA DOS GRÃOS, PERNAMBUCO - Silva, A. M. C. (Revista Nordestina de Zoologia, 2013)
The study area comprised the beaches of Fort Orange, Florida, Lime Kiln, Pilar, Jaguaribe and Quiet in Itamaracá. This article focuses on dynamic relationships among agents from the beach and interstitial fauna of sediments. From November 2003 to October 2004 monthly samples were taken. The interstitial fauna samples were collected in estirâncio in an imaginary square 1m x 1m with five replicates collected at the ends and center of the square, in low tide, totaling 360 samples. The sediment samples were monthly for each beach and also collected the transect, totalizando 72 samples. Feituras of beach profiles were performed and their graphs made according to the absolute reference frame of each. The meiofauna was composed , according to the evolutionary order by: Nematoda, Rotifero, Tardigrada, Polychaeta, Oligochaeta, Acari, Ostracoda, Copepoda and Mollusca, and Nematoda, Oligochaeta and Copepoda representatives of the dominant fauna; Polychaeta and how abundant Ostracoda, Rotifera as a common and tardigrades, Acari and Mollusca as rare. The study of the distribution of praiais sediments revealed the occurrence of facies quartz sands fine to medium. The morphology shows the beaches of São Paulo, Lime Kiln, Pilar, Jaguaribe and Quiet with a tendency to erosion and beach of Forte Orange with depositional trend. The variation of the sediment budget of the beaches was the determining factor for the quantitative composition of the meiofauna in the whole period.